Intent to obtain pediatric influenza vaccine among mothers in four middle income countries. Issue 27 (2nd June 2020) - Wagner, Abram L.; Gordon, Aubree; Tallo, Veronica L.; Simaku, Artan; Porter, Rachael M.; Edwards, Laura J.; Duka, Enkeleda; Abu-Khader, Ilham; Gresh, Lionel; Sciuto, Cristina; Azziz-Baumgartner, Eduardo; Bino, Silvia; et al.
Highlights: Mothers in Albania, Nicaragua, Philippines, and Jordan completed a survey. Influenza vaccine is not routinely given in these countries. Many mothers were unaware of the disease or vaccine. Perceived safety was an important predictor of vaccine intentions. Abstract: Background: Despite a large burden of influenza in middle income countries, pediatric vaccination coverage remains low. The aims of this study were to (1) describe mothers' knowledge and attitudes about influenza illnesses and vaccination, and (2) identify characteristics associated with mothers' intent to vaccinate their child. Methods: From 2015 to 2017, infants 0–11 months old in Nicaragua, Philippines, Jordan, and Albania were enrolled from community settings and hospitals. Interviewers administered a questionnaire to their mothers. Mothers of infants aged 6–11 months rated their intention (small-to-moderate vs. large chance) to accept pediatric vaccination if it was offered at no-cost. The importance of knowledge, attitudes, and sociodemographic characteristics in predicting influenza vaccination intention was measured as the mean decrease in Gini index when that factor was excluded from 1000 decision trees in a random forest analysis. Results: In total, 1, 308 mothers were enrolled from the community setting and 3, 286 from the hospital setting. Prevalence of at least some knowledge of influenza illness ranged from 34% in Philippines to 88% in Albania (in the community sample), and between 23% in Philippines to 88% in Jordan (in the hospital sample). In the community sample, most mothers in Albania (69%) and Philippines (58%) would accept the influenza vaccine, and these proportions were higher in the hospital sample for all countries except Albania (48%) (P < 0.0001). Perceived vaccine safety (mean decrease in Gini index = 61) and effectiveness (55), and perceived knowledge of influenza vaccine (45) were the most important predictors of influenza vaccination intention in models that also included country and community versus hospital sample. Conclusion: Intent to vaccinate infants aged 6–11 months in four middle income countries was tied primarily to knowledge of the vaccine and perceptions of vaccine safety and effectiveness. These findings were noted among mothers interviewed in the community and mothers of recently hospitalized infants.